The mediating roles of screen time and sleep duration in the association between extracurricular physical activity and visual acuity in primary school students - Jilin Li; Yang Wang; Xuehui Zhang; Ye Chen; Li Xi (Frontiers in Public Health, 2026)
Objective This study aimed to examine the association between extracurricular physical activity (EPA) and visual acuity (VA) among primary school students in Macau and investigate the mediating roles of screen time (ST) and sleep duration (SD). Methods A stratified random cluster sampling method was used to recruit primary school students in Macau ( n = 2,098). Data were collected using questionnaire surveys. Pearson correlation analysis and structural equation modeling were conducted. Results EPA, ST, SD, and VA were significantly correlated ( p < 0.01). Mediation analysis identified a direct association between EPA and VA and indirect associations through ST and SD. The estimated total association was 0.129 (95% CI [0.099, 0.162]), and the total indirect association through ST and SD was 0.058 (95% CI [0.039, 0.082]), accounting for 44.96% of the estimated total association. The specific indirect associations through SD and ST were 0.033 (95% CI [0.020, 0.052]) and 0.022 (95% CI [0.010, 0.037]), accounting for 25.58 and 17.05% of the estimated total association, respectively. The sequential indirect association through ST and SD was statistically significant but small (0.003, 95% CI [0.001, 0.006]), accounting for 2.33% of the estimated total association. Conclusion EPA was positively correlated with VA among primary school students, and statistically detectable indirect associations were observed through ST, SD, and the sequential ST–SD pathway.